Ultra-refractory mantle within oceanic plateau: Petrology of the spinel harzburgites from Lac Michèle, Kerguelen Archipelago - Wasilewski, B.; Doucet, Luc-Serge; Moine, B.; Beunon, H.; Delpech, G.; Mattielli, N.; Debaille, V.; Delacour, A.; Grï goire, M.; Guillaume, D.; Cottin, J. (Elsevier BV, 2017)
The study presents major and trace element compositions of whole-rocks and minerals of 24 spinel harzburgite xenoliths from the Lac Michèle locality in the northern part of the Kerguelen Archipelago (South Indian Ocean). The samples are modally homogeneous and large enough to provide representative whole-rock samples. Their Mg# are high (0.91 to 0.93) and they have 16–29 wt.% orthopyroxene (opx) and low clinopyroxene contents (0.1–2.8 wt.%). They display a wide range of serpentinisation, which result in LOI contents ranging from 0 to 3.5 wt.%. The spinel-bearing harzburgites from Lac Michèle are the most refractory peridotites identified so far among peridotite xenoliths available on the Kerguelen Archipelago and within the oceanic lithosphere. By contrast with most of the peridotite xenoliths from Kerguelen, they have been more preserved from post-formation processes such as metasomatic processes. The major and trace element compositions of the least serpentinised spinel harzburgites indicate an origin by ~ 30% of polybaric decompression fractional melting between 5GPa and ≤ 1 GPa. Thus, the spinel harzburgites from Lac Michèle, situated at the top of the Kerguelen lithospheric mantle, are residues of melting that took place over a broad range of depth and mostly in the garnet stability field. Our results, in comparison with published data on mantle xenoliths worldwide, show that spinel harzburgites from Lac Michèle have major and modal compositions that fall in the range of cratonic peridotites rather than abyssal peridotites, oceanic island peridotites, subduction zones peridotites and off-cratonic peridotites. This indicates (i) they formed in similar condition as for the ancient continental lithospheric mantle or (ii) they are fragment of ancient continental lithospheric mantle incorporated in the Kerguelen plateau.